Rebranding Unit Bisnis Digital sebagai Strategi Komersialisasi Pondok Pesantren Lubbul Labib Maron - Ainul Yakin; Misbahul Arifin; Mohammad Dendy Musthofa (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study analyzes the digital-based business unit rebranding strategy as a solution to the financial crisis faced by Lubbul Labib Islamic Boarding School, Probolinggo Regency, East Java. The financial crisis, which resulted in a budget deficit of up to 40 percent, prompted the institution to transform from a conventional funding system toward ethical commercialization through digitalization of productive business units. The research employs a qualitative approach with a case study design, collecting data through in-depth interviews with 12 informants, three months of participatory observation, and analysis of institutional strategic documents. Data were analyzed using the Miles and Huberman interactive model with gradual reduction, presentation, and conclusion-drawing techniques. Findings indicate that the implementation of rebranding strategies through social media platforms and digital marketplaces successfully increased business unit revenue threefold and expanded market reach across islands. The transformation's success depends on three crucial mechanisms: theological legitimation from religious authority figures, establishment of sharia-based ethical boundaries in business operations, and reframing entrepreneurship as an instrument of student pedagogy. The commercialization process generated value negotiations between profit orientation and the maintenance of educational and Islamic propagation missions, which were resolved through open dialogue and transparency in profit allocation for student scholarships. The research contributes by integrating theories of digital entrepreneurship, social entrepreneurship, and Islamic economics into a contextual Islamic boarding school entrepreneurship model, providing practical implications in the form of digital transformation guidelines for Islamic educational institutions to achieve sustainable financial independence without neglecting their religious identity.